Enam Karakter Profil Pelajar Pancasila dan Implikasinya Terhadap Ketahanan Pribadi Siswa - Sri Florina Laurence Zagoto; I Wayan Suastra (Journal Prakarsa Paedagogia, 2024)
Nowadays, national problems continue to emerge in the world of education, including intolerance which violates the values of Pancasila. Therefore, the Ministry of Education and Culture continues to strive to overcome these various problems. One of the efforts made was to initiate the Pancasila Student Profile, a profile of the ideal Indonesian student, of course according to Pancasila. The aim of this research is to find out more about what the Pancasila Student Profile is, and what its implications are for students' personal resilience. The method used in this research is a qualitative method. The research results show that the Pancasila Student Profile includes noble character, independence, critical reasoning, creativity, mutual cooperation and global diversity. The Pancasila Student Profile has implications for students' personal resilience because it directs students to become individuals with character in accordance with Pancasila which is summarized in a Pancasila Student Profile.